Caracterização das formas de organização da produção pecuária e das modalidades de ocorrência da Febre Aftosa nas mesorregiões homogêneas central mineira e oeste de MInas, 1980 a 1994 - Marieta Cristina Madureira Frois (1995)
The organizational forms ofthe animal production and the modes of occurrence of foot-aud-mouth (FMD) in the regions ofthe state of Minas Gerais known as Central Mineira and Oeste de Minas were characterized. in the period from 1980 to 1994. The analysis was performed using demographic, ecologic and economic indicators, identifying the regions with common behaviour. It was found that the municipalities of these regions show forms of organization of animal production and outbreads of FMD which once distinct from each other A primary endemic area for FMD was identified, corresponding to farms breadiug and raising catlle up to I year of age and farms with the complete cycle of production. A secundary endemic area for FMD wich corresponds to farms raising catlle for fattening was additionally identiiied. It was concluded that the control of FMD showed be based on adoption of differentiated strategic measures for each the areas. in order to meet the ideal of animal health expected.